Gamma Knife irradiation method based on dosimetric controls to target small areas in rat brains. Issue 5 (15th April 2015) - Constanzo, Julie; Paquette, Benoit; Charest, Gabriel; Masson‐Côté, Laurence; Guillot, Mathieu
Abstract : Purpose: Targeted and whole‐brain irradiation in humans can result in significant side effects causing decreased patient quality of life. To adequately investigate structural and functional alterations after stereotactic radiosurgery, preclinical studies are needed. The purpose of this work is to establish a robust standardized method of targeted irradiation on small regions of the rat brain. Methods: Euthanized male Fischer rats were imaged in a stereotactic bed, by computed tomography (CT), to estimate positioning variations relative to the bregma skull reference point. Using a rat brain atlas and the stereotactic bregma coordinates obtained from CT images, different regions of the brain were delimited and a treatment plan was generated. A single isocenter treatment plan delivering ≥100 Gy in 100% of the target volume was produced by Leksell GammaPlan using the 4 mm diameter collimator of sectors 4, 5, 7, and 8 of the Gamma Knife unit. Impact of positioning deviations of the rat brain on dose deposition was simulated by GammaPlan and validated with dosimetric measurements. Results: The authors' results showed that 90% of the target volume received 100 ± 8 Gy and the maximum of deposited dose was 125 ± 0.7 Gy, which corresponds to an excellent relative standard deviation of 0.6%. This dose deposition calculated with GammaPlan was validated with dosimetric films resulting in a dose‐profile agreement within 5%, both in X ‐ and Z ‐axes. Conclusions: The authors' results demonstrate the feasibility of standardizing the irradiation procedure of a small volume in the rat brain using a Gamma Knife.